Image Content Verification based on DWT and Chaotic Map Watermarking - Alshibani, Dina Riadh; Sadeq, Zinah (Iraqi Journal of Science, 2018)
Image content verification is to confirm the validity of the images, i.e. . To test if the image has experienced any alteration since it was made. Computerized watermarking has turned into a promising procedure for image content verification in light of its exceptional execution and capacity of altering identification. In this study, a new scheme for image verification reliant on two dimensional chaotic maps and Discrete Wavelet Transform (DWT) is introduced. Arnold transforms is first applied to Host image (H) for scrambling as a pretreatment stage, then the scrambled host image is partitioned into sub-blocks of size 2×2 in which a 2D DWT is utilized on each sub-block to produce corresponding sub-block of DWT coefficients (LL, LH, HL and HH). Meanwhile, watermark image is encrypted using the introduced chaos-based enciphering algorithm. The watermarked image is obtained by updating the approximation coefficients (LH sub-band) of each 2×2 sub-block of DWT coefficients of the host image with the enciphered watermark image bits. Different investigational tests are performed to evaluate the act of the introduced approach. Investigation results clearly present that the proposed approach can detect and localize editing attacks perfectly.